Biological indicator attributes of soil quality under cultivated and natural pasture in the Pantanal wetlands - Cardoso, Evaldo Luis; Silva, Marx Leandro Naves; Moreira, Fátima Maria de Souza; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the changes in the biological attributes of soil promoted by substitution of the native forest by cultivated pasture, and by the submission of native pasture under continuous grazing in the Pantanal wetlands. The work consisted of the evaluation of three native forests, three Brachiaria decumbens pastures of different formation ages, established in substitution to the native forests and three native pastures, one under continuous grazing and two without grazing for 3 and 19 years. Soil samples were collected at 0–10 and 10–20 cm depths, in the three 100-m transects in each sampled site. Each transect represented one replicate. The following attributes were evaluated: total organic carbon (TOC), soil microbial carbon (Cmic), microbial quotient (qMIC), basal respiration (BR) and metabolic quotient (qCO2). The substitution of the native forest by cultivated pasture reduced TOC, Cmic, and qMIC and increased BR. The continuous grazing on native pasture reduced TOC and Cmic contents. Cmic was the most sensitive attribute to the alterations imposed on soil by the cultivated and native pasture systems, since it was marked by more substantial reductions.